High Frequency Electrotherapy for the Treatment of Meibomian Gland Dysfunction. Issue 11 (November 2019) - Ferrari, Giulio; Colucci, Annalisa; Barbariga, Marco; Ruggeri, Alfredo; Rama, Paolo
Abstract : Purpose: To test the safety and efficacy of high frequency electrotherapy (ET) on the clinical signs and symptoms of patients affected by dry eye and meibomian gland dysfunction (MGD). Methods: Twenty-five patients affected by MGD were enrolled. Quantum Molecular Resonance ET was administered by means of the Rexon-Eye device 4 times, once per week for 4 weeks. Patients were reexamined 1 month after the last treatment. The primary endpoint was reduction in corneal fluorescein staining. Additional endpoints were tear break-up time, Ocular Surface Disease Index score, meibomian gland secretion score, and the number of expressible meibomian glands. Safety endpoints were Logarithm of the Minimum Angle of Resolution (LogMar) best spectacle-corrected visual acuity and intraocular pressure. Results: Corneal fluorescein staining improved by 62.5% ( P < 0.0001), tear breakup time increased by 30.9% ( P < 0.0001), and the Ocular Surface Disease Index score improved by 37% ( P < 0.001). The meibum quality and the number of expressible meibomian glands also increased (35.7% and 12%, P < 0.001 and P < 0.0001, respectively). Schirmer test scores increased after treatment by 16.5% ( P = 0.01). No adverse events were observed. Conclusions: Quantum Molecular Resonance ET appears to be safe and significantly reduces symptoms and signs associated with MGD. It may have a relevant role in the treatment of evaporative dry eye disease.